Vasoinhibin, an N-terminal Prolactin Fragment, Directly Inhibits Cardiac Angiogenesis in Three-dimensional Heart Culture - Nakajima, Ryojun; Nakamura, Eri; Harigaya, Toshio (Frontiers in Endocrinology, 2017)
Vasoinhibins (Vis) are fragments of the growth hormone/prolactin family and have antiangiogenic functions in many species. It is considered that Vis derived from prolactin are involved in the pathogenesis of peripartum cardiomyopathy (PPCM). However, the pathogenic mechanism of PPCM, as well as heart angiogenesis, is not yet clear. Therefore, the aim of the present study was to clarify the effects of Vis on endothelial cells and angiogenesis of the heart. Endothelial cell viability was decreased by Vi treatment in a culture experiment. Furthermore, expression of proangiogenic genes, such as vascular endothelial growth factor, endothelial nitric oxide synthase, and VE-cadherin, were decreased. On the other hand, apoptotic factor gene, caspase 3, and inflammatory factor genes, tumor necrosis factor α and interleukin 6, were increased by Vi treatment. In three-dimensional left ventricular wall angiogenesis assay in mice, Vi treatment also inhibited cell migration, neovessel sprouting, and growth toward collagen gel. These data demonstrate that Vi treatment directly suppresses angiogenesis of the heart and supports the hypothesis that Vis induce PPCM.